The black family and the search for freedom: the importance of collectivity in the struggle for manumission (Guarapiranga, 1850 - 1888) (Ágora Journal, 2025)
The main objective of this text is to defend the importance of the 19th century black family as a privileged space for freedom struggle. For this, we defend the conception that the black population has successfully articulated networks of sociability, family and kinship, to achieve better living conditions, including the so desired freedom. In this sense, we will present the importance of the family piranguense for the development of legal processes of freedom, which were mobilized in the region between 1850 and 1888. By bringing our documentary data, together with a bibliography on the subject, we aimed to show that family ties could be strategically instrumentalized, in order to contribute to the freedom of family members.
Keywords: Freedom suits; Black family; Networks of sociability.